Genomic Analysis of Multidrug-Resistant Hypervirulent (Hypermucoviscous) Klebsiella pneumoniae Strain Lacking the Hypermucoviscous Regulators (rmpA/rmpA2) - Hisham N. Altayb; Hana S. Elbadawi; Othman Baothman; Imran Kazmi; Faisal A. Alzahrani; Muhammad Shahid Nadeem; Salman Hosawi; Kamel Chaieb (Antibiotics, 2022)
Hypervirulent K. pneumoniae (hvKP) strains possess distinct characteristics such as hypermucoviscosity, unique serotypes, and virulence factors associated with high pathogenicity. To better understand the genomic characteristics and virulence profile of the isolated hvKP strain, genomic data were compared to the genomes of the hypervirulent and typical K. pneumoniae strains. The K. pneumoniae strain was isolated from a patient with a recurrent urinary tract infection, and then the string test was used for the detection of the hypermucoviscosity phenotype. Whole-genome sequencing was conducted using Illumina, and bioinformatics analysis was performed for the prediction of the isolate resistome, virulome, and phylogenetic analysis. The isolate was identified as hypermucoviscous, type 2 (K2) capsular polysaccharide, ST14, and multidrug-resistant (MDR), showing resistance to ciprofloxacin, ceftazidime, cefotaxime, trimethoprim-sulfamethoxazole, cephalexin, and nitrofurantoin. The isolate possessed four antimicrobial resistance plasmids (pKPN3-307_type B, pECW602, pMDR, and p3K157) that carried antimicrobial resistance genes (ARGs) (blaOXA-1,blaCTX-M-15, sul2, APH(3″)-Ib, APH(6)-Id, and AAC(6′)-Ib-cr6). Moreover, two chromosomally mediated ARGs (fosA6 and SHV-28) were identified. Virulome prediction revealed the presence of 19 fimbrial proteins, one aerobactin (iutA) and two salmochelin (iroE and iroN). Four secretion systems (T6SS-I (13), T6SS-II (9), T6SS-III (12), and Sci-I T6SS (1)) were identified. Interestingly, the isolate lacked the known hypermucoviscous regulators (rmpA/rmpA2) but showed the presence of other RcsAB capsule regulators (rcsA and rcsB). This study documented the presence of a rare MDR hvKP with hypermucoviscous regulators and lacking the common capsule regulators, which needs more focus to highlight their epidemiological role.